2002
DOI: 10.4269/ajtmh.2002.66.86
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Coxiella burnetii by a centrifugation shell-vial assay from ticks collected in Cyprus: detection by nested polymerase chain reaction (PCR) and by PCR-restriction fragment length polymorphism analyses.

Abstract: Abstract. Ticks are the principal vectors and reservoirs of Coxiella burnetii. The identification of isolates is necessary for understanding the clinical diversity of Q fever in different geographic areas. This is the first report of isolation of C. burnetii from ticks by the shell-vial assay and by nested polymerase chain reaction (PCR) assay for the detection of this pathogen in ticks. Of 141 ticks collected in Cyprus (Rhipicephalus sanguineus and Hyalloma spp.), 10% were found to be infected with C. burneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The reference strain Nine Mile was isolated from a tick in the USA [36]. C. burnetii is able to infect more than 40 species of ticks but their role in the transmission of the disease seems to be variable according to the country [82,89,104,150]. In France, this principally concerns wild and seldom concerns farm animals [83].…”
Section: Zoonotic Aspectmentioning
confidence: 99%
“…The reference strain Nine Mile was isolated from a tick in the USA [36]. C. burnetii is able to infect more than 40 species of ticks but their role in the transmission of the disease seems to be variable according to the country [82,89,104,150]. In France, this principally concerns wild and seldom concerns farm animals [83].…”
Section: Zoonotic Aspectmentioning
confidence: 99%
“…For example, the soft ticks Ornithodoros (Almeida et al, 2012) and Carios (Reeves et al, 2006) were found to harbour this bacterium. Hard ticks, such as Amblyomma , Rhipicephalus (Bernasconi et al, 2002), Dermacentor (Psaroulaki et al, 2006), Ixodes (Spitalska and Kocianova, 2003), Hyalomma (Spyridaki et al, 2002) and Haemaphysalis, have also been found to be infected by Coxiella endosymbionts (MachadoFerreira et al, 2011). This indicates that Coxiella-like bacteria colonise a great variety of hosts for survival and reproduction.…”
Section: Introductionmentioning
confidence: 97%
“…Polymerase Chain Reaction (PCR) and PCR-based techniques are reported to be sensitive and specific for the detection of C. burnetii from tick samples (3,17,29,31). C. burnetii were found in Ixodes ricinus (24,29), Dermacentor reticulatus (24), D. marginatus (1,23,29), Haemaphysalis concinna (24,29), H. punctata (24), H. inermis (24), H. sulcata (27), H. longicornis (13), Rhipicephalus sanguineus (3,5,22,27), R. turanicus (3,27), Ambylomma variegatum (16), Hyalomma spp.…”
Section: Introductionmentioning
confidence: 99%
“…C. burnetii were found in Ixodes ricinus (24,29), Dermacentor reticulatus (24), D. marginatus (1,23,29), Haemaphysalis concinna (24,29), H. punctata (24), H. inermis (24), H. sulcata (27), H. longicornis (13), Rhipicephalus sanguineus (3,5,22,27), R. turanicus (3,27), Ambylomma variegatum (16), Hyalomma spp. (5,22) by using conventional (23) and PCR techniques (3,5,29,31).…”
Section: Introductionmentioning
confidence: 99%